Influencia de factores sociodemográficos en la actitud del estudiante de educación sobre donación de órganos del donante cadavérico. 2012 - Espejo Coria, Jhoselim Denisse (2012)
The present study is a descriptive cross-sectional, was conducted during the month of July 2012, the Faculty of Education at the Universidad National de Trujillo (UNT), in order to determine the influence of sociodemographic factors on the attitude of student education about organ donation. The sample consisted of 826 high school students, and the sample by 213, who answered the questionnaire on sociodemographic and attitude about organ donation from deceased donors; being the information obtained, processed and analyzed using: the statistical test "Chi Square" and the results are presented in tables and graphs. After the analysis has led to the following conclusions: according to socio-demographic factors: 50.7 percent of students at UNT Education were males and 49.3 females, 39.9 percent are over 25 years, 54.5 percent belong to the 4th and 5th year, 50.7 percent are Catholic and 86.4 percent are single, 60.1 percent of education students at UNT have indifferent attitude about organ donation; There is significant influence between the variables: sex (p = 0.0014), age (p = 0.0437), education (p = 0.0438), religion (p = 0.02) and marital status (p = 0.0105), with the attitude about organ donation in students of the faculty of education at UNT.